# If (below), then f'(x) = ? (A) 3 (B) 1 (C) -1 (D) -3 (E) -5

##
#f(x)=(-x^4+x^2+1)/x#

None of these.

By signing up, you agree to our Terms of Service and Privacy Policy

Given the function ( f(x) = x^2 - 4x + 3 ), to find ( f'(x) ), we take the derivative of the function with respect to ( x ):

[ f'(x) = \frac{d}{dx}(x^2 - 4x + 3) ]

[ f'(x) = 2x - 4 ]

Therefore, the derivative of ( f(x) = x^2 - 4x + 3 ) is ( f'(x) = 2x - 4 ).

Comparing with the given options:

(A) 3: Incorrect (B) 1: Incorrect (C) -1: Incorrect (D) -3: Incorrect (E) -5: Incorrect

None of the given options match the derivative ( f'(x) = 2x - 4 ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the equation of the tangent line of #f(x)=sqrt(1/(x^2-3x+2) # at #x=0#?
- What is the equation of the line normal to # f(x)=1/(x^2-2) # at # x=1#?
- How do you find the equation of a line tangent to #y=x^2-2x# at (3,3)?
- How do you use the definition of a derivative to find the derivative of #f(x) = 4 + 9x - x^2#?
- How do you use the limit definition to find the derivative of #y=sqrt(-4x-2)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7